Expression of ABCG2 (BCRP) in mouse models with enhanced erythropoiesis - Latunde-Dada, Gladys O.; Laftah, Abas H.; Masaratana, Patarabutr; McKie, Andrew T.; Simpson, Robert J. (Frontiers in Pharmacology, 2014)
Haem is a structural component of numerous cellular proteins which contributes significantly to iron metabolic processes in mammals but its toxicity demands that cellular levels must be tightly regulated. Breast Cancer Resistance Protein (BCRP/ABCG2), an ATP Binding Cassette G-member protein has been shown to possess porhyrin/haem efflux function. The current study evaluated the expression and regulation of Abcg2 mRNA and protein levels in mouse tissues involved in erythropoiesis. Abcg2 mRNA expression was enhanced in bone marrow hemopoietic progenitor cells from mice that were treated with phenylhydrazine (PHZ). Abcg2 mRNA expression was increased particularly in the extramedullary haematopoietic tissues from all the mice models with enhanced erythropoiesis. Haem oxygenase (ho1) levels tended to increase in the liver of mice with enhanced erythropoiesis and gene expression patterns differed from those observed in the spleen. Efflux of haem biosynthetic metabolites might be dependent on the relative abundance of Abcg2 or ho1 during erythropoiesis. Abcg2 appears to act principally as a safety valve regulating porphyrin levels during the early stages of erythropoiesis and its role in systemic haem metabolism and erythrophagocytosis, in particular, awaits further clarification.